Diagnosis Value of Colposcope Combined with Serum Squamous Cell Carcinoma Antigen, Carbohydrate Antigen 125, and Carcinoembryonic Antigen for Moderate to Advanced Cervical Cancer Patients Treated with Modified Fuzheng Peiyuan Decoction. (31st December 2021) - Meng, Huijuan; Zhang, Yulan; Chen, Youguo
Abstract : Objective . To explore the diagnosis value of colposcope combined with serum squamous cell carcinoma antigen (SCC-Ag), carbohydrate antigen 125 (CA125), and carcinoembryonic antigen (CEA) for moderate to advanced cervical cancer patients treated with modified Fuzheng Peiyuan decoction. Methods . The clinical data of 43 moderate to advanced cervical cancer patients treated in Suzhou Hospital of Traditional Chinese Medicine from July 2018 to July 2019 were selected for the retrospective analysis, and 43 healthy women undergoing physical examination in our medical center in the same period were selected as the control group. The cervical cancer patients accepted the modified Fuzheng Peiyuan decoction treatment, the detection of SCC-Ag, CA125, and CEA and colposcope examination were performed to all research subjects, and the changes in indicators such as KPS scores and lesion perfusion parameters in cervical cancer patients before and after treatment were monitored, so as to analysis the clinical diagnosis value of combined diagnosis in treated patients. Results . After treatment, the mean KPS scores were greatly higher and various blood perfusion parameters of lesions and serum SCC-Ag, CA125, and CEA levels were remarkably lower than before (P value <0.001 for all); the area under the curve of combined test was significantly larger than that of single test, and the sensitivity and specificity of the combined test were the highest; and after medication, the total incidence rate of toxic and side effects was 11.63%. Conclusion . Fuzheng Peiyuan decoction has significant effect in treating moderate to advanced cervical cancer, and colposcope combined with serum test presents more accurate and credible diagnosis results and has great significance for future treatment, which shall be promoted and applied.